Bibliometric Analysis of γδ T Cells as Immune Regulators in Cancer Prognosis - Liu, Bing; He, Xu; Wang, Yong; Huang, Jian-wen; Zheng, You-bing; Li, Yong; Lu, Li-gong (Frontiers in Immunology, 2022)
γδ T cells are one of only three immune cell types that express antigen receptors that undergo somatic recombination, and they contribute to immune responses to infection, cellular transformation, and tissue damage. As a “bridge” between the innate and adaptive immune systems, γδ T cells have been noted to be involved in various immune responses during cancer progression. The purpose of our study was to review current published information on γδ T cells and investigate their functions in different types of malignancy using bibliometric and bioinformatic methods. Our results indicated that studies on γδ T cells and cancer progression increased from 2014, and the number had peaked by 2021. We discovered that there is international cooperation in the performance of studies among 26 countries, where China was identified as the most productive with the highest citations. Using keyword co-occurrence analysis, we found that among all the cancer types investigated, gastric and breast cancers were most closely related to γδ T cells. Furthermore, interleukin (IL)-17 and IL-2 were the most common cytokines linked to γδ T cells and our investigation of their potential involvement in the prognosis of gastric and breast cancers, identified their different roles in various malignancies. Thus, we concluded that γδ T cells might influence the progression of different cancers in diverse ways.